Zirconium-free titanium-free quartz ceramic tile ground coat and preparation method of ceramic tile using ground coat

By using high-purity, high-whiteness ultrafine quartz powder without zirconium or titanium in the ceramic tile base glaze, combined with ball milling and prefiring treatment, the existing ceramic tile base glaze has solved the problems of high cost and unstable cost, and achieved low cost , wide firing range and high stability ceramic tile base glaze.

CN119430653AActive Publication Date: 2025-02-14JIANGXI WONDERFUL CERAMICS CO LTD +3
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411667788.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The use of zirconium and titanium emulsion glaze in existing ceramic tile base glazes has problems such as high cost, high radioactivity, narrow firing range and unstable firing range, which is difficult to meet the low cost, high stability and wide firing range of the ceramic industry. demand.

Method used

Using high-purity, high-whiteness, ultrafine quartz powder without zirconium and titanium as the main component of the base glaze, the specific gravity of the glaze slurry is adjusted to form an emulsion effect, combined with prefiring and grinding treatment, reduce free quartz and improve melt viscosity. , generates a stable emulsion crystal phase.

Benefits of technology

It has achieved a zirconium-free and titanium-free ceramic tile base glaze, with low cost, wide firing range, uniform whiteness and glossiness, and high stability, meeting the use requirements of ceramic tile.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a zirconium-free titanium-free quartz ceramic tile ground coat and a preparation method of a ceramic tile using the ground coat. The zirconium-free titanium-free quartz ceramic tile ground coat is prepared from the following components in parts by weight: 5 to 8 parts of talc, 6 to 8 parts of wollastonite, 10 to 20 parts of potassium feldspar, 0 to 3 parts of calcined kaolin, 8 to 10 parts of kaolin, 35 to 40 parts of nepheline syenite and 18 to 22 parts of high-purity high-whiteness quartz powder. The invention relates to a high-temperature-resistant glass which is prepared from the following chemical components in percentage by weight: 2.07 to 3.87 percent of LOI (LOI), 2.64 to 64.25 percent of SiO2 (SiO2), 18.47 to 19.34 percent of Al2O3 (Al2O3), 0.10 to 0.32 percent of Fe2O3 (Fe2O3), 2.67 to 4.75 percent of CaO (CaO), 2.05 to 2.38 percent of MgO (MgO), 2.07 to 2.15 percent of K2O (K2O) and 5.02 to 7.17 percent of Na2O (Na2O). The zirconium-free titanium-free quartz ceramic tile ground coat provided by the invention is low in cost, wide in firing range and uniform in color development, the whiteness after firing can reach 66-72 degrees, and the glossiness is 4-7 degrees.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building ceramics, and particularly relates to a zirconium-free and titanium-free quartz-based ceramic tile bottom glaze and a method for preparing a ceramic tile using the bottom glaze. Background Art

[0002] In the building ceramics industry, base glaze (also known as cosmetic clay) has been widely used because it "can cover the color and some defects of the ceramic body, has a strong concealing effect, reduces the requirements of the body for the selection of raw materials, and can greatly reduce product costs." Based on years of industry production experience, in order to achieve the concealing effect and ensure the quality of the product in the later stage, the requirements for base glaze are generally controlled at a whiteness of 55 to 70° and a glossiness of 4 to 10° after firing.

[0003] At present, the base glazes used in the industry mainly include zirconium opacified base glaze and titanium opacified base glaze. Although the radioactivity of zirconium opacified base glaze is relatively high, its refractive index is as high as 1.93-2.01, which has a good opacifying effect, high whiteness, strong wear resistance, can broaden the firing temperature range of glaze, and is not affected by the firing atmosphere. However, since my country has not yet found a stable and high-quality zircon sand source, most of the zircon sand raw materials used in the ceramic industry rely on imports, and are highly dependent on the international market. In addition, with the continuous rise in global commodity prices in recent years, the price of zircon sand has also continued to rise, greatly increasing the cost of ceramic companies, forcing ceramic process technicians to use various technical means to find substitutes for zirconium silicate in the increasingly fierce market competition and reduce the comprehensive cost of base glaze.

[0004] On the other hand, in order to eliminate the radioactive radiation hazards caused by the radioactive substances associated with the raw materials of zirconium silicate and alleviate the pressure of relying on imported zircon sand resources, in recent years, most industry technicians have focused on the research of low-cost, non-radioactive titanium-based opalescent base glazes, such as CN111499202A, CN109293238A, CN115304277A, CN116040945B, etc. CN111499202A discloses a high solar reflectivity opalescent glaze and a preparation method thereof, which controls the calcium-titanium molar ratio in the opalescent glaze within a certain range, thereby promoting the oxidation of titanium dioxide and Calcite reacts to form titanophosphite during the firing process, which prevents titanium dioxide from existing in the rutile phase at high temperatures and causing the glaze to turn yellow. However, this technical solution of using titanophosphite grains as seeds to induce the reaction of titanium dioxide and calcite to form titanophosphite crystal phases with a particle size of 450 to 600 nm requires the addition of a large amount of calcite, and the base glaze must be melted for a complete reaction. This will cause the base glaze to have a very high gloss after firing at actual kiln temperatures, deviating from the empirical principle that the gloss of the base glaze used in ceramic production is generally controlled at 4 to 10°, resulting in a lower minimum eutectic point of the glaze composition in the opalescent glaze and a narrower melting temperature range, which is prone to defects such as glaze pinholes and prickly heat. The titanium dioxide opaque base glaze and ceramic plate disclosed in CN115304277A need to first prepare a titanium dioxide frit as an opacifier, and then strictly control the content of alumina and calcium in the formula, so that titanium dioxide and wollastonite can react in a solid phase to synthesize titanite without allowing titanium dioxide to exist in the rutile crystal form during a firing process with an ambient temperature of 1100-1150°C and a firing period of 60 minutes, thereby better suppressing the tendency of rutile titanium dioxide to turn yellow and preventing the glaze from turning yellow. However, the firing range is too narrow and is not suitable for platform transformation. CN116040945B discloses a ceramic tile base glaze, ceramic tile and preparation method thereof, wherein metatitanic acid and brucite are introduced into the ceramic tile base glaze formula, and a magnesium titanate milky phase is generated through a solid phase reaction, the glaze gloss is less than 10 degrees, and the whiteness is between 60 and 70 degrees, which is looser than the base glaze containing titanium dioxide frit, and can be fired at a high temperature of 1150 to 1250°C for use. However, in fact, the stability of the product is not enough. After a long period of sunlight exposure, the glaze surface of the product will still turn yellow in the later stage. In summary, the milky base glaze containing titanium components is not stable enough when used on a high temperature platform (firing temperature>1000°C), and there is always a risk of discoloration. Summary of the invention

[0005] The technical problem solved by the present invention is to overcome the deficiencies existing in the above-mentioned prior art, and to provide a base glaze formula which does not contain zirconium, is non-radioactive, does not rely on imported raw materials, and has relatively low cost, thereby solving the problem of high cost and high radioactivity caused by whitening with zirconium silicate. At the same time, the base glaze formula also does not contain titanium, thereby solving the problem of titanium-based glaze opacity base glaze having a narrow firing range, instability, and easy discoloration, and providing a high-white zirconium-free and titanium-free quartz-based ceramic tile base glaze. Another technical problem solved by the present invention is to provide a method for preparing a zirconium-free and titanium-free quartz-based ceramic tile base glaze by applying low-cost, high-purity and high-whiteness ultrafine quartz powder to ceramic base glaze, utilizing the ultrafine quartz powder's particle-like form to enable the ultrafine quartz powder to act as an emulsifier in the glaze, so that the glaze forms an opacifying effect, thereby achieving zirconium-free and titanium-free whitening of the base glaze, and having a stable structure and a wide firing range, which is beneficial to saving high-quality ceramic raw material resources. The high-purity and high-whiteness quartz powder used is pre-fired before grinding to reduce the presence of free quartz. In the subsequent firing preparation process of the product, the nepheline in the formula can melt quartz, increase the viscosity of the melt, generate a relatively stable opacifying crystal phase, achieve a good opacifying effect, and promote the technology and development of the ceramic industry. Another technical problem solved by the present invention is to provide a high-white zirconium-free and titanium-free quartz ceramic tile base glaze with low cost, wide firing range and uniform color. The whiteness after firing can reach 66-72° and the glossiness is 4-7°. A method for preparing ceramic tiles using the zirconium-free and titanium-free quartz ceramic tile base glaze that meets the use requirements of the base glaze.

[0006] The technical solution of the present invention is the zirconium-free and titanium-free quartz ceramic tile base glaze, which is special in that it is composed of the following components by weight: 5 to 8 parts of talc, 6 to 8 parts of wollastonite, 10 to 20 parts of potassium feldspar, 0 to 3 parts of calcined kaolin, 8 to 10 parts of kaolin, 35 to 40 parts of nepheline syenite, and 18 to 22 parts of high-purity high-white quartz powder; the corresponding chemical composition is composed of the following components by weight percentage: LOI 2.07 to 3.87%, SiO2 62.64 to 64.25%, Al2O3 18.47 to 19.34%, Fe2O3 0.10 to 0.32%, CaO 2.67 to 4.75%, MgO 2.05 to 2.38%, K2O 2.07 to 2.15%, and Na2O 5.02 to 7.17%.

[0007] Preferably, the ceramic tile base glaze is further composed of the following components by weight: 5 parts of talc, 6.5 parts of wollastonite, 20 parts of potassium feldspar, 2 parts of calcined kaolin, 8 parts of kaolin, 36 parts of nepheline powder, and 18 parts of high-purity high-white quartz powder; the corresponding chemical composition is composed of the following components by weight percentage: LOI 2.17%, SiO2 64.21%, Al2O3 19.24%, Fe2O30.13%, CaO 4.75%, MgO 2.35%, K2O 2.11%, and Na2O 5.04%.

[0008] Preferably, the nepheline powder is a powdery object ground from nepheline syenite, with a fineness of 325 mesh and a water-soluble salt content of <1%. The chemical composition of the nepheline powder is composed of the following components by weight percentage: LOI 5.07%, SiO243.33%, Al2O3 28.50%, Fe2O3 0.36%, CaO 4.96%, MgO 0.03%, K2O 4.58%, and Na2O13.17%.

[0009] Preferably, the high-purity and high-white quartz powder is quartz powder with SiO2 content>95%, Fe2O3 content<0.1%, and whiteness>85°. The chemical composition of the high-purity and high-white quartz powder is composed of the following components by weight percentage: SiO2 98.23%, Fe2O3 0.05%, Al2O3 1.5%, K2O 0.1%, Na2O 0.12%; whiteness is: 92°.

[0010] As a preferred method, the method for preparing high-purity high-white quartz powder comprises the following steps:

[0011] ⑴ The quartz sand is graded and screened, and iron is removed through screening to remove the metal, wood and clay mixed therein, and the quartz sand with a particle size of 5 to 20 mm is selected;

[0012] (2) The quartz sand obtained by screening is pickled: the solution used for pickling is hydrochloric acid HCl and oxalic acid H2C2O4, which are mixed and diluted in a ratio of 1:1, with a concentration of 15%. The quartz sand is soaked in the mixed solution for 3 to 4 days. During the soaking process, an electric stirrer is used for stirring to ensure that the quartz sand is fully in contact with the acid solution to remove the iron on the surface of the quartz sand;

[0013] ⑶ Filtration;

[0014] (4) Whitening the quartz sand: soak the acid-washed quartz sand in tap water containing a fluorescent whitening agent for 15 to 20 minutes, wherein the fluorescent whitening agent is a water-based fluorescent whitening agent RQT-C-3, and the addition ratio is 1 / 10,000 to 5 / 10,000;

[0015] ⑸ Use tap water to wash and filter repeatedly;

[0016] (6) Dry and pre-burn the high-purity and high-white quartz sand obtained by filtration at a temperature of 850-980°C for 3 hours;

[0017] (7) Grinding: Grind the pre-burned high-purity and high-white quartz sand with a Raymond mill until the particle size distribution is D10 = 1.31 μm, D25 = 1.56 μm, D50 = 2.94 μm, D75 = 2.44 μm, and D90 = 3.25 μm.

[0018] Another technical solution of the present invention is a method for preparing the zirconium-free and titanium-free quartz ceramic tile bottom glaze, which is special in that it includes the following steps:

[0019] ⑴ Weigh the materials according to the formula and put them into the ball mill, then add 40% water, and grind them to a fineness of 0.5-0.7% on a 325 mesh sieve;

[0020] (2) Adjust the glaze slurry to a specific gravity of 1.80-1.84;

[0021] ⑶ The performance of the obtained zirconium-free and titanium-free quartz ceramic tile base glaze was tested: its expansion coefficient at 400°C was measured to be 7.33×10 -06 / ℃, the melting temperature is 1105℃, and the expansion coefficient corresponding to the melting temperature is 8.73×10 -06 / ℃, close to the conventional green body expansion coefficient;

[0022] (4) Conduct a single trial firing experiment on the zirconium-free and titanium-free quartz ceramic tile base glaze: Take the zirconium-free and titanium-free quartz ceramic tile base glaze and pour it on the ceramic body with a glaze thickness of 0.7-1.0mm. Firing is carried out under the firing system of firing temperature of 1070-1180℃ and firing time of 40-60min. The product glaze has a whiteness and glossiness of 4-7° and a whiteness of 66-72°, which meets the use requirements of the base glaze.

[0023] Another technical solution of the present invention is a method for preparing ceramic tiles using zirconium-free and titanium-free quartz ceramic tile bottom glaze, which is special in that it includes the following steps:

[0024] ⑴Body pressing;

[0025] ⑵ Drying, drying temperature: 180~210℃;

[0026] ⑶ Apply zirconium-free and titanium-free quartz ceramic tile base glaze with a glaze thickness of 0.7 to 1.0 mm;

[0027] ⑷Inkjet printing decoration;

[0028] ⑸ Pour transparent glaze. The transparent glaze can be matte glaze, glossy glaze, full-polished glaze, protective glaze or anti-slip glaze according to the requirements of product development on gloss and texture;

[0029] (6) High temperature sintering: sintering temperature is 1070~1180℃, sintering time is 40~60min. In order to ensure that the high-purity and high-white quartz powder is completely melted at high temperature and achieve a good emulsification effect, 8 sintering high temperature zones are set at 1165~1180℃.

[0030] As preferred: the step (3) further comprises:

[0031] (3.1) Weigh the materials according to the formula and place them into a ball mill. Add 40% water and grind them to a fineness of 0.5-0.7% on a 325-mesh sieve;

[0032] (3.2) Adjust the glaze slurry to a specific gravity of 1.80 to 1.84;

[0033] (3.3) The performance of the obtained zirconium-free and titanium-free quartz ceramic tile base glaze was tested: its expansion coefficient at 400°C was measured to be 7.33×10 -06 / ℃, the melting temperature is 1105℃, and the expansion coefficient corresponding to the melting temperature is 8.73×10 -06 / ℃, close to the conventional green body expansion coefficient;

[0034] (3.4) A single trial firing experiment was conducted on the zirconium-free and titanium-free quartz ceramic tile base glaze: the zirconium-free and titanium-free quartz ceramic tile base glaze was poured on the ceramic body with a glaze thickness of 0.7 to 1.0 mm. The base glaze was fired at a firing temperature of 1070 to 1180°C and a firing time of 40 to 60 min. The product had a glaze whiteness and glossiness of 4 to 7° and a whiteness of 66 to 72°, which met the requirements for the base glaze.

[0035] The fourth technical solution of the present invention is a method for preparing high-purity and high-white quartz powder in the zirconium-free and titanium-free quartz ceramic tile bottom glaze, which is special in that it includes the following steps:

[0036] ⑴ The quartz sand is graded and screened, and iron is removed through screening to remove the metal, wood and clay mixed therein, and the quartz sand with a particle size of 5 to 20 mm is selected;

[0037] (2) The quartz sand obtained by screening is pickled: the solution used for pickling is hydrochloric acid HCl and oxalic acid H2C2O4, which are mixed and diluted in a ratio of 1:1, with a concentration of 15%. The quartz sand is soaked in the mixed solution for 3 to 4 days. During the soaking process, an electric stirrer is used for stirring to ensure that the quartz sand is fully in contact with the acid solution to remove the iron on the surface of the quartz sand;

[0038] ⑶ Filtration;

[0039] (4) Whitening the quartz sand: soak the pickled quartz sand in tap water containing a fluorescent whitening agent for 15 to 20 minutes to allow the whitening agent factor to adhere to the surface of the quartz sand and achieve the purpose of whitening the quartz sand. The fluorescent whitening agent is a water-based fluorescent whitening agent RQT-C-3, and the addition ratio is 1 / 10,000 to 5 / 10,000;

[0040] ⑸ Use tap water to wash and filter repeatedly;

[0041] (6) Dry and pre-burn the high-purity and high-white quartz sand obtained by filtration at a temperature of 850-980°C for 3 hours. Pre-burning can reduce free quartz and obtain a more stable crystal phase.

[0042] (7) Grinding: Grind the pre-burned high-purity and high-white quartz sand with a Raymond mill until the particle size distribution is D10 = 1.31 μm, D25 = 1.56 μm, D50 = 2.94 μm, D75 = 2.44 μm, and D90 = 3.25 μm.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The high-white zirconium-free and titanium-free quartz ceramic tile base glaze of the present invention has a cost of 2,200 yuan / ton, which saves 500 yuan / ton compared with the conventional zirconium silicate base glaze costing 2,700 yuan / ton. It has low cost, can be adapted to firing at a temperature of 1070 to 1180°C, has a wide firing range, is easy to control firing, has uniform color, and has more stable quality. The whiteness after firing can reach 66 to 72°, and the glossiness is 4 to 7°, which meets the use requirements of the base glaze.

[0045] (2) The base glaze formula of the present invention does not contain zirconium element, is non-radioactive, does not rely on imported raw materials, and has relatively low cost, which solves the problem of high cost and high radioactivity caused by whitening with zirconium silicate. The base glaze formula of the present invention also does not contain titanium element, which solves the problem of narrow firing range, instability, and easy discoloration of the opaque base glaze of titanium-based glazes.

[0046] ⑶ The present invention applies low-cost, high-purity and high-whiteness ultrafine quartz powder to ceramic base glaze. The ultrafine quartz powder has a microparticle shape, so that the ultrafine quartz powder can play the role of an emulsifier in the glaze, so that the glaze forms an emulsified effect, and the base glaze is whitened without zirconium and titanium, with a stable structure and a wide firing range, which is beneficial to saving high-quality ceramic raw material resources and promoting the technology and development of the ceramic industry.

[0047] ⑷ The high-purity and high-white quartz powder used in the present invention is pre-burned before grinding to reduce the presence of free quartz. In the subsequent firing preparation process of the product, the nepheline in the formula can melt the quartz, increase the viscosity of the melt, generate a relatively stable emulsified crystal phase, and achieve a good emulsification effect. DETAILED DESCRIPTION

[0048] The present invention will be further described in detail below in conjunction with embodiments:

[0049] Embodiment 1:

[0050] The zirconium-free and titanium-free quartz ceramic tile base glaze is composed of the following components by weight: 5 parts of talc, 6.5 parts of wollastonite, 20 parts of potassium feldspar, 2 parts of calcined kaolin, 8 parts of kaolin, 36 parts of nepheline powder, and 18 parts of high-purity high-white quartz powder; the corresponding chemical composition is composed of the following components by weight percentage: LOI 2.17%, SiO2 64.21%, Al2O3 19.24%, Fe2O30.13%, CaO 4.75%, MgO 2.35%, K2O 2.11%, and Na2O 5.04%.

[0051] The nepheline powder is a powdery object ground from nepheline syenite, with a fineness of 325 meshes and a water-soluble salt content of <1% so as not to cause thixotropy of the glaze slurry;

[0052] The chemical composition of the nepheline powder consists of the following components by weight percentage: IL 5.07%, SiO2 43.33%, Al2O3 28.50%, Fe2O3 0.36%, CaO 4.96%, MgO 0.03%, K2O 4.58%, Na2O 13.17%;

[0053] The addition of nepheline powder to the formula is to adjust the expansion coefficient of the base glaze, strengthen the bonding degree between the body and the glaze, and ensure that the brick shape is within a controllable range. Secondly, at high temperatures, nepheline can melt quartz, increase the viscosity of the melt, and generate a more stable milky crystal phase.

[0054] The high-purity and high-white quartz powder is quartz powder with SiO2 content>95%, Fe2O3 content<0.1%, and whiteness>85°. The chemical composition of the high-purity and high-white quartz powder is composed of the following components by weight percentage: SiO298.23%, Fe2O3 0.05%, Al2O3 1.5%, K2O 0.1%, Na2O 0.12%; the whiteness is: 92°.

[0055] The method for preparing high-purity and high-white quartz powder comprises the following steps:

[0056] ⑴ The quartz sand is graded and screened, and iron is removed through screening to remove the metal, wood and clay mixed therein, and the quartz sand with a particle size of 5 to 20 mm is selected;

[0057] (2) The quartz sand obtained by screening is pickled: the solution used for pickling is hydrochloric acid HCl and oxalic acid H2C2O4, which are mixed and diluted in a ratio of 1:1, with a concentration of 15%. The quartz sand is soaked in the mixed solution for 3 days. During the soaking process, an electric stirrer is used for stirring to ensure that the quartz sand is fully in contact with the acid solution to remove the iron on the surface of the quartz sand;

[0058] ⑶ Filtration;

[0059] (4) Whitening the quartz sand: soak the pickled quartz sand in tap water containing a fluorescent whitening agent for 20 minutes to allow the whitening agent factor to adhere to the surface of the quartz sand and achieve the purpose of whitening the quartz sand. The fluorescent whitening agent is a water-based fluorescent whitening agent RQT-C-3, and the addition ratio is 0.02%;

[0060] ⑸ Use tap water to wash and filter repeatedly;

[0061] (6) Dry and pre-burn the high-purity and high-white quartz sand obtained by filtration at a temperature of 880±10°C for 3 hours. Pre-burning can reduce free quartz and obtain a more stable crystal phase.

[0062] (7) Grinding: Grind the pre-burned high-purity and high-white quartz sand with a Raymond mill until the particle size distribution is D10 = 1.31 μm, D25 = 1.56 μm, D50 = 2.94 μm, D75 = 2.44 μm, and D90 = 3.25 μm.

[0063] The method for preparing zirconium-free and titanium-free quartz ceramic tile bottom glaze comprises the following steps:

[0064] ⑴ Weigh the materials according to the formula and put them into the ball mill, then add 40% water, and grind them to a fineness of 0.58%±0.02% on a 325-mesh sieve;

[0065] (2) Adjust the glaze slurry to a specific gravity of 1.82±0.02;

[0066] ⑶ The performance of the obtained zirconium-free and titanium-free quartz ceramic tile base glaze was tested: its expansion coefficient at 400°C was measured to be 7.33×10 -06 / ℃, the melting temperature is 1105℃, and the expansion coefficient corresponding to the melting temperature is 8.73×10 -06 / ℃, close to the conventional green body expansion coefficient;

[0067] (4) Conduct a single trial firing experiment on the zirconium-free and titanium-free quartz ceramic tile base glaze: Take the zirconium-free and titanium-free quartz ceramic tile base glaze and pour it on the ceramic body with a glaze thickness of 0.8±0.05mm. Firing is carried out under the firing system of firing temperature 1165±10℃ and firing time 55min. The product glaze has a whiteness and glossiness of 5~6° and a whiteness of 68~69°, which meets the use requirements of the base glaze.

[0068] The method for preparing ceramic tiles using zirconium-free and titanium-free quartz ceramic tile bottom glaze comprises the following steps:

[0069] ⑴Body pressing;

[0070] ⑵ Drying, drying temperature: 200±5℃;

[0071] ⑶ Apply zirconium-free and titanium-free quartz ceramic tile base glaze with a glaze thickness of 0.8±0.05mm;

[0072] ⑷Inkjet printing decoration;

[0073] ⑸ Apply transparent glaze. The transparent glaze can be matte glaze according to the requirements of gloss and texture in product development;

[0074] (6) High temperature sintering: sintering temperature is 1165±10℃, sintering time is 55min. In order to ensure that the high-purity and high-white quartz powder is completely melted at high temperature and achieve a good emulsification effect, 8 sintering high temperature zones are set at 1165~1175℃.

[0075] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.

Claims

1. A zirconium-free and titanium-free quartz ceramic tile base glaze, characterized in that: The invention is composed of the following components by weight: 5-8 parts of talc, 6-8 parts of wollastonite, 10-20 parts of potassium feldspar, 0-3 parts of calcined kaolin, 8-10 parts of kaolin, 35-40 parts of nepheline syenite, and 18-22 parts of high-purity high-white quartz powder; the corresponding chemical composition is composed of the following components by weight percentage: LOI 2.07-3.87%, SiO2 62.64-64.25%, Al2O3 18.47-19.34%, Fe2O3 0.10-0.32%, CaO 2.67-4.75%, MgO2.05-2.38%, K2O 2.07-2.15%, and Na2O 5.02-7.17%.

2. The zirconium-free and titanium-free quartz ceramic tile base glaze according to claim 1, characterized in that: The ceramic tile base glaze is further composed of the following components by weight: 5 parts of talc, 6.5 parts of wollastonite, 20 parts of potassium feldspar, 2 parts of calcined kaolin, 8 parts of kaolin, 36 parts of nepheline powder, and 18 parts of high-purity high-white quartz powder; the corresponding chemical composition is composed of the following components by weight percentage: LOI 2.17%, SiO2 64.21%, Al2O3 19.24%, Fe2O3 0.13%, CaO 4.75%, MgO 2.35%, K2O 2.11%, and Na2O 5.04%.

3. The zirconium-free and titanium-free quartz ceramic tile base glaze according to claim 1 or 2, characterized in that: The nepheline powder is a powdery object ground from nepheline syenite, with a fineness of 325 mesh and a water-soluble salt content of <1%. The chemical composition of the nepheline powder is composed of the following components by weight percentage: LOI 5.07%, SiO2 43.33%, Al2O3 28.50%, Fe2O30.36%, CaO 4.96%, MgO 0.03%, K2O 4.58%, and Na2O 13.17%.

4. The zirconium-free and titanium-free quartz ceramic tile base glaze according to claim 1 or 2, characterized in that: The high-purity and high-white quartz powder is quartz powder with SiO2 content>95%, Fe2O3 content<0.1%, and whiteness>85°. The chemical composition of the high-purity and high-white quartz powder is composed of the following components by weight percentage: SiO2 98.23%, Fe2O3 0.05%, Al2O3 1.5%, K2O 0.1%, Na2O 0.12%; whiteness is: 92°.

5. The zirconium-free and titanium-free quartz ceramic tile base glaze according to claim 1, characterized in that: The method for preparing high-purity and high-white quartz powder comprises the following steps: ⑴ The quartz sand is graded and screened, and iron is removed through screening to remove the metal, wood and clay mixed therein, and the quartz sand with a particle size of 5 to 20 mm is selected; (2) The quartz sand obtained by screening is pickled: the solution used for pickling is hydrochloric acid HCl and oxalic acid H2C2O4, which are mixed and diluted in a ratio of 1:1, with a concentration of 15%. The quartz sand is soaked in the mixed solution for 3 to 4 days. During the soaking process, an electric stirrer is used for stirring to ensure that the quartz sand is fully in contact with the acid solution to remove the iron on the surface of the quartz sand; ⑶ Filtration; (4) Whitening the quartz sand: soak the acid-washed quartz sand in tap water containing a fluorescent whitening agent for 15 to 20 minutes, wherein the fluorescent whitening agent is a water-based fluorescent whitening agent RQT-C-3, and the addition ratio is 1 / 10,000 to 5 / 10,000; ⑸ Use tap water to wash and filter repeatedly; (6) Dry and pre-burn the high-purity and high-white quartz sand obtained by filtration at a temperature of 850-980°C for 3 hours; (7) Grinding: Grind the pre-burned high-purity and high-white quartz sand with a Raymond mill until the particle size distribution is D10 = 1.31 μm, D25 = 1.56 μm, D50 = 2.94 μm, D75 = 2.44 μm, and D90 = 3.25 μm.

6. A method for preparing a zirconium-free and titanium-free quartz ceramic tile bottom glaze, characterized in that: The following steps are involved: ⑴ Weigh the materials according to the formula and put them into the ball mill, then add 40% water, and grind them to a fineness of 0.5-0.7% on a 325-mesh sieve; (2) Adjust the glaze slurry to a specific gravity of 1.80-1.84; ⑶ The performance of the obtained zirconium-free and titanium-free quartz ceramic tile base glaze was tested: its expansion coefficient at 400°C was measured to be 7.33×10 -06 / ℃, the melting temperature is 1105℃, and the expansion coefficient corresponding to the melting temperature is 8.73×10 -06 / ℃, close to the conventional green body expansion coefficient; (4) Conduct a single trial firing experiment on the zirconium-free and titanium-free quartz ceramic tile base glaze: Take the zirconium-free and titanium-free quartz ceramic tile base glaze and pour it on the ceramic body with a glaze thickness of 0.7-1.0mm. Firing is carried out under the firing system of firing temperature of 1070-1180℃ and firing time of 40-60min. The product glaze has a whiteness and glossiness of 4-7° and a whiteness of 66-72°, which meets the use requirements of the base glaze.

7. A method for preparing ceramic tiles using zirconium-free and titanium-free quartz-based ceramic tile base glaze, characterized in that: The following steps are involved: ⑴Body pressing; ⑵ Drying, drying temperature: 180~210℃; ⑶ Apply zirconium-free and titanium-free quartz ceramic tile base glaze with a glaze thickness of 0.7 to 1.0 mm; ⑷Inkjet printing decoration; ⑸ Pour transparent glaze. The transparent glaze can be matte glaze, glossy glaze, full-polished glaze, protective glaze or anti-slip glaze according to the requirements of product development on gloss and texture; (6) High temperature sintering: sintering temperature is 1070~1180℃, sintering time is 40~60min. In order to ensure that the high-purity and high-white quartz powder is completely melted at high temperature and achieve a good emulsification effect, 8 sintering high temperature zones are set at 1165~1180℃.

8. The method for preparing ceramic tiles using zirconium-free and titanium-free quartz-based ceramic tile bottom glaze according to claim 7, characterized in that: The step (3) further comprises: (3.1) Weigh the materials according to the formula and place them into a ball mill. Add 40% water and grind them to a fineness of 0.5-0.7% on a 325-mesh sieve; (3.2) Adjust the glaze slurry to a specific gravity of 1.80 to 1.84; (3.3) The performance of the obtained zirconium-free and titanium-free quartz ceramic tile base glaze was tested: its expansion coefficient at 400°C was measured to be 7.33×10 -06 / ℃, the melting temperature is 1105℃, and the expansion coefficient corresponding to the melting temperature is 8.73×10 -06 / ℃, close to the conventional green body expansion coefficient; (3.4) A single trial firing experiment was conducted on the zirconium-free and titanium-free quartz ceramic tile base glaze: the zirconium-free and titanium-free quartz ceramic tile base glaze was poured on the ceramic body with a glaze thickness of 0.7 to 1.0 mm. The base glaze was fired at a firing temperature of 1070 to 1180°C and a firing time of 40 to 60 min. The product had a glaze whiteness and glossiness of 4 to 7° and a whiteness of 66 to 72°, which met the requirements for the base glaze.

9. A method for preparing high-purity and high-white quartz powder in zirconium-free and titanium-free quartz ceramic tile bottom glaze, characterized in that: The following steps are involved: ⑴ The quartz sand is graded and screened, and iron is removed through screening to remove the metal, wood and clay mixed therein, and the quartz sand with a particle size of 5 to 20 mm is selected; (2) The quartz sand obtained by screening is pickled: the solution used for pickling is hydrochloric acid HCl and oxalic acid H2C2O4, which are mixed and diluted in a ratio of 1:1, with a concentration of 15%. The quartz sand is soaked in the mixed solution for 3 to 4 days. During the soaking process, an electric stirrer is used for stirring to ensure that the quartz sand is fully in contact with the acid solution to remove the iron on the surface of the quartz sand; ⑶ Filtration; (4) Whitening the quartz sand: soak the pickled quartz sand in tap water containing a fluorescent whitening agent for 15 to 20 minutes to allow the whitening agent factor to adhere to the surface of the quartz sand and achieve the purpose of whitening the quartz sand. The fluorescent whitening agent is a water-based fluorescent whitening agent RQT-C-3, and the addition ratio is 1 / 10,000 to 5 / 10,000; ⑸ Use tap water to wash and filter repeatedly; (6) Dry and pre-burn the high-purity and high-white quartz sand obtained by filtration at a temperature of 850-980°C for 3 hours. Pre-burning can reduce free quartz and obtain a more stable crystal phase. (7) Grinding: Grind the pre-burned high-purity and high-white quartz sand with a Raymond mill until the particle size distribution is D10 = 1.31 μm, D25 = 1.56 μm, D50 = 2.94 μm, D75 = 2.44 μm, and D90 = 3.25 μm.

Citation Information

Patent Citations

  • High-content syenite low-cost zirconium-free opaque glaze and preparation method and application thereof

    CN109293238A

  • Opacified glaze with high sunlight reflectivity and preparation method thereof

    CN111499202A

  • Titanium white opaque ground coat and ceramic plate

    CN115304277A

  • Ceramic tile bottom glaze, ceramic tile and preparation method thereof

    CN116040945B

  • Zirconium-free ultra-white overglaze and preparation method thereof

    CN110128016A